Pericatheter Leak Associated With Earlier Peritoneal Dialysis Initiation Does Not Influence Long-Term Outcomes - George Tsihlis; Kieren Pirabhahar; Frederika Sciberras; MaryAnn Nicdao; Laraine Aw; Alvie Agoo; Vincent Lee; Jennifer Li; Lukas Kairaitis; Kamal Sud; Jan Swinnen; Katrina Chau (Kidney International Reports)
Introduction: Internationally, peritoneal dialysis (PD) is increasingly being commenced within 2 weeks of catheter insertion. Studies are warranted to evaluate outcomes of this strategy. Methods: This study examines outcomes of early-start PD (ESPD) and conventional-start PD (CSPD), commencing at ≤14 days and >14 days after catheter insertion, respectively. All adults with kidney failure within a large metropolitan PD unit initiating PD through a new catheter, inserted using laparoscopic or modified Seldinger technique, between August 2019 and August 2022, were included in this retrospective observational study. Demographic data and episodes of infectious and mechanical complications were collected using electronic medical records. Analysis was conducted using analysis of variance and Chi-square testing. A P-value < 0.05 was significant with Bonferroni correction performed where relevant. Kaplan-Meier and competing risks analyses were performed for time to PD-related peritonitis and transfer to hemodialysis. Results: A total of 297 patients (70% male, mean age 58.7 years) were included, with 130 (43.8%) patients undertaking ESPD. Most patients had laparoscopically inserted catheters (65.3%) and 65 patients (22.0%) received prior hemodialysis. When compared to CSPD, ESPD was associated with a higher number of pericatheter leaks (6.9% vs. 0.6%, P = 0.003), with otherwise similar complication episodes and no significant difference with respect to time to PD-related peritonitis or transfer to hemodialysis. Catheter insertion technique or prior hemodialysis treatment did not significantly influence outcomes. Conclusion: ESPD is associated with increased pericatheter leaks when compared to CSPD, with an otherwise similar complication profile.